CONTENT OF NPK HARA INGREDIENTS IN LIQUID ORGANIC FERTILIZER FROM VARIOUS TYPES OF RICE WASHING - Sulfianti Sulfianti; Eko Priyantono; Risman Risman (Universitas Tadulako, 2021)
This research aims to assess the NPK nutrient content of liquid organic fertilizers from various types of rice washing water. This research was conducted in September 2020 at Sidondo III Village, Sigi Biromaru District, Sigi Regency and the Soil Laboratory of the Faculty of Agriculture, Tadulako University. This study was designed using a completely randomized design (CRD) with 5 treatments, namely P0 (without rice water), P1 (white rice washing water), P2 (white glutinous rice washing water), P3 (black glutinous rice washing water), and P4 (red glutinous rice washing water), the treatment was repeated 4 times so that there were 20 experimental units. The observation parameters in this research were the observation of temperature, pH, POC color, and aroma of POC during the fermentation process as well as the N, P, and K content in the resulting POC. The results showed that the treatment with the addition of washing water for white glutinous rice (P2) produced the highest content compared to other treatments with an N content of 0.15%, but in the observation of P and K content, the addition of washing water for red glutinous rice (P4) gave the results. the highest with a P content of 0.09% and K of 0.14% but not different from the addition of washing water for white glutinous rice (P2).